Alpha-Lipoic Acid Promotes Intestinal Epithelial Injury Repair by Regulating MAPK Signaling Pathways - Yang, Yu; Xiao, Yong; Jiang, Yue; Luo, Jiajun; Yuan, Jingwen; Yan, Junfeng; Tong, Qiang (Mediators of Inflammation, 2022)
Intestinal epithelial cells are an essential barrier in human gastrointestinal tract, and healing of epithelial wound is a key process in many intestinal diseases. α-Lipoic acid (ALA) was shown to have antioxidative and anti-inflammatory effects, which could be helpful in intestinal epithelial injury repair. The effects of ALA in human colonic epithelial cells NCM460 and human colorectal adenocarcinoma cells Caco-2 were studied. ALA significantly promoted NCM460 and Caco-2 migration, increased mucosal tight junction factors ZO-1 and OCLN expression, and ALA accelerated cell injury repair of both cells in wound healing assay. Western blot analysis indicated that ALA inhibited a variety of mitogen-activated protein kinase (MAPK) signaling pathways in the epithelial cells. In conclusion, ALA was beneficial to repair of intestinal epithelial injury by regulating MAPK signaling pathways.